Development Of Education In Palembang In 1942-1950 (Contribution Of Learning Materials For The Course Of History Of Education) - Pandu Wiranata; Sani Safitri; Alian Alian (Sriwijaya University in collaboration with Perkumpulan Program Studi Pendidikan Sejarah Se-Indonesia (P3SI) dan Masyarakat Sejarawan Indonesia (MSI)., 2018)
This research entitled